'There is a very distinct need for education' among people with rotator cuff tendinopathy: An exploration of health professionals' attitudes. (February 2020) - White, Jennifer; Auliffe, Sean Mc; Jepson, Megan; Burstein, Frada; Hopman, Ruben; Morrissey, Dylan; Haines, Terence; Malliaras, Peter
Abstract: Background: Clinical practice guidelines recommend non-surgical care in the management of rotator cuff tendinopathy prior to considering imaging or surgery. However, this requires effective education to promote adherence to treatment. Objectives: To explore expert shoulder clinician's experiences with managing rotator cuff tendinopathy including practice beliefs towards providing education. Design: An in-depth qualitative study. Method: We conducted interviews (n = 8) with an international sample of expert shoulder clinician-researchers. Data were analysed using an inductive thematic approach with constant comparison. Results: Three key themes emerged: (1) The need for early, focused education: "Some beliefs can be detrimental to rehabilitation options", (2) Developing therapeutic alliance: "If a patients trust you then you are generally going to get much better results" and (3) What is required moving forward in current day RT management: "Maybe we can get better." Conclusions: Our findings highlight the importance of education to alleviate potential barriers to effective conservative care (including exercise) and self-management for rotator cuff tendinopathy. We also identified actionable ways to promote a collaborative therapeutic alliance however, this hinges on sufficient clinical time to educate patients adequately, which may be a barrier in busy clinical settings. Further, there is need for targeted education to facilitate development of clinical skills required to implement effective patient education strategies. Highlights: Health literacy skills can be enhanced through patient education. Clinicians benefit from training in providing education. There is a need for organisational leaders to better support patient centred care.